On the performance of bioadsorption processes for heavy metal ions removal by low-cost agricultural and natural by-products bioadsorbent: a review - Al-Qodah, Z; Yahya, MA; Al-Shannag, M (Desalination Publications, 2024)
Indexed by WOS/ Scopus